The structure and interpretation of the standard model - McCabe, Gordon; ScienceDirect eBooks (Amsterdam ; Oxford : Elsevier, 2007)
This book provides a philosophically informed and mathematically rigorous introduction to the 'standard model' of particle physics. The standard model is the currently accepted and experimentally verified model of all the particles and interactions in our universe. All the elementary particles in our universe, and all the non-gravitational interactions -the strong nuclear force, the weak nuclear force, and the electromagnetic force - are collected together and, in the case of the weak and electromagnetic forces, unified in the standard model. Rather than presenting the calculational recipes favored in most treatments of the standard model, this text focuses upon the elegant mathematical structures and the foundational concepts of the standard model. Combines an exposition of the philosophical foundations and rigorous mathematical structure of particle physics Demonstrates the standard model with elegant mathematics, rather than a medley of computational recipes Promotes a group-theoretical and fibre-bundle approach to the standard model, rather than the Lagrangian approach favoured by calculationalists Explains the different approaches to particle physics and the standard model which can be found within the literature.
Preface -- 1. Introduction -- 2. Matter Fields -- 3. Gauge Fields -- 4. Interactions -- 5. Standard Model Gauge Groups and Representations -- 6. The Standard Model Interacting Particle bundle -- Appendices -- Index.
Includes bibliographical references and index.
Print version record.
Elsevier
Keywords: Particles (Nuclear physics); Standard model (Nuclear physics); SCIENCE -- Physics -- Nuclear; SCIENCE -- Physics -- Atomic & Molecular; Particles (Nuclear physics); Standard model (Nuclear physics); Standardmodell; Electronic books